ANALISIS SKILL CHANGE BERBASIS WORKSHOP PADA KELOMPOK USAHA MIKRO KECIL DAN MENENGAH (UMKM) BORDIR GAMPONG SIDOREJO KOTA LANGSA - Maulidal Khairi; Nurlaila Hanum; Safuridar Safuridar; Rini Mastuti (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to find out how hard skills and soft skills change in the embroidery MSME group in Gampong Sidorejo, Langsa City before and after the Workshop activities. In this study the authors used a qualitative descriptive research type, with data collection methods through observation, interviews and documentation. MSMEs are an important part of the economy of a nation. The activities carried out in MSME activities are producing goods and trading in order to obtain large profits/income, but previously in order to produce quality goods, MSME groups must have adequate HR skills. The results showed that workshops can provide skill changes to the HR of the MSME group, which is seen from the level of knowledge and skills regarding the technique of designing embroidery motifs, the mothers of the MSME embroidery group have begun to understand the techniques of designing embroidery motifs and are able to make beautiful embroidery motif designs. At the level of increasing sales revenue, it can be seen that there was an increase in income of around 50% after the workshop activities were held. The economic growth of the people of Gampong Sidorejo, Langsa City, especially the embroidery MSME group, is at a good level, this is measured by an increase in embroidery production and income in the community's economic activities.